Exposure of CCRF‐CEM cells to acridone derivative 8a triggers tumor death via multiple mechanisms. Issue 7 (14th March 2016) - Wang, Yini; Gao, Dan; Chu, Bizhu; Gao, Chunmei; Cao, Deliang; Liu, Hongxia; Jiang, Yuyang
Abstract : A newly synthesized acridone derivative8a shows potent antitumor activity against CCRF‐CEM leukemia cells. Herein, the first proteomic study of8a effects in CCRF‐CEM cells was performed by 2D nano‐LC‐ESI‐MS/MS to better understand the mechanisms of action of8a . Data analyses based on PLGS, STRING, Cytoscape, and database for annotation, visualization, and integrated discovery identified 55 proteins that were differentially expressed in response to8a exposure. Multiple cellular pathways were affected, including chromatin organization, energy metabolism, DNA repair, oxidative‐stress, and apoptosis. The changes in protein expression were further verified for PKM2. Moreover, 8a lowered down the expression of HEX and PFK‐1. Lactate production was decreased in8a‐ treated cells, indicating suppression of glycolysis. The elevated XRCC6 and decreased histone expression levels suggested increased DNA damage in8a‐ treated cells, which was confirmed by the increased γ‐H2AX foci. Molecular docking of8a with DNA demonstrated direct interactions of8a with DNA through three hydrogen bonds and four π–π interactions, potentially explaining the mode of action that8a damaged to DNA. The differential protein profiling and dysfunction of metabolic pathways induced by8a provide novel insights into the potential action mechanisms of8a .